A Grammar of Politics - LASKI, Harold J. (George Allen & Unwin LTD, 1951)
Laski’s magnum opus, this volume outlines the history and functions of state institutions which (in the author’s view) are desirable for the effective functioning of a democracy. Topics discussed include: The necessity of government; state and society; rights and power; liberty and equality; property as a theory of industrial organisation; the nature of nationalism; law as a source of authority; the functions of international organisations.